A fever in the heartland eaudiobook The ku klux klan's plot to take over america, and the woman who stopped them. - Egan, Timothy (Books on Tape, 2023)
"With meticulous detective work, Timothy Egan shines a light on one of the most sinister chapters in American history—how a viciously racist movement, led by a murderous conman, rose to power in the early twentieth century. A Fever in the Heartland is compelling, powerful, and profoundly resonant today." — David Grann, author of THE WAGER and KILLERS OF THE FLOWER MOON A historical thriller by the Pulitzer and National Book Award-winning author that tells the riveting story of the Klan's rise to power in the 1920s, the cunning con man who drove that rise, and the woman who stopped them. The Roaring Twenties—the Jazz Age—has been characterized as a time of Gatsby frivolity. But it was also the height of the uniquely American hate group, the Ku Klux Klan. Their domain was not the old Confederacy, but the Heartland and the West. They hated Blacks, Jews, Catholics and immigrants in equal measure, and took radical steps to keep these people from the American promise. And the man who set in motion their takeover of great swaths of America was a charismatic charlatan named D.C. Stephenson. Stephenson was a magnetic presence whose life story changed with every telling. Within two years of his arrival in Indiana, he’d become the Grand Dragon of the state and the architect of the strategy that brought the group out of the shadows – their message endorsed from the pulpits of local churches, spread at family picnics and town celebrations. Judges, prosecutors, ministers, governors and senators across the country all proudly proclaimed their membership. But at the peak of his influence, it was a seemingly powerless woman – Madge Oberholtzer – who would reveal his secret cruelties, and whose deathbed testimony finally brought the Klan to their knees. A FEVER IN THE HEARTLAND marries a propulsive drama to a powerful and page-turning reckoning with one of the darkest threads in American history. Photo courtesy of The Indiana Album: Evan Finch Collection.